Description Competencies of Medical Surgical Nursing Preceptors at Naval Center Hospital Dr. Ramelan Surabaya, Indonesia - Imroatul Farida; Putri, Wahyu Rizka Yolanda; Syihab, Bahtyar Hardyansyah (Asian Journal of Applied Education (AJAE), 2024)
This study evaluated the competence of preceptors in surgical medical nursing. The research method uses quantitative descriptive with a cross-sectional research design. The sample number was 100 respondents doing clinical practice in medical-surgical nursing at the Navy Central Hospital. Dr. Ramelan Surabaya. The sampling technique uses Simple Random Sampling. The questionnaire used is the Preceptor Competency Questionnaire, which is a self-assessment. The results showed that all preceptors had good competence in all indicators. These indicators include knowledge competence, clinical skills, teaching ability, communication skills, personal characteristics, leadership, professional behavior, and ethics. However, a small percentage of receptors need to improve the ease of consultation. This research provides new insights into the practice of clinical guidance in surgical medical nursing. It can be applied to enhance the quality of clinical learning in hospitals and nursing education institutions.